“Ya no podemos tapar el sol con las manos…”. Cambio Climático, Ministerio Público y la Opinión Consultiva 32/25 de la CIDH - Marchisio, Adrián (Revista Internacional de Direito Público | RIDP, 2026)
This paper analyzes Advisory Opinion 32/25 of the Inter-American Court of Human Rights, a landmark decision that recognizes climate change as a legal reality generating concrete obligations for States. The Court established that its impacts directly and indirectly affect fundamental rights such as life, health, water, housing, and a healthy environment, thereby consolidating environmental ius cogens and the principle of intergenerational equity. The article connects these developments with the best available science—particularly the IPCC reports—and with international instruments such as the United Nations Framework Convention on Climate Change and the Escazú Agreement. It also examines convergence with other international tribunals (UN Human Rights Committee, ECtHR, ITLOS, ICJ) and underscores the role of public participation and the Public Prosecutor’s Office as a guarantor of collective interests. Ultimately, it argues for the consolidation of the right to a healthy climate as an operational principle within the Inter-American system, advancing towards genuine climate justice.